Antidiabetic, hypolipidemic and hepatoprotective effects of Arctium lappa root's hydro-alcoholic extract on nicotinamide-streptozotocin induced type 2 model of diabetes in male mice - Akram Ahangarpour; Hamid Heidari; Ali Akbar Oroojan; Farhang Mirzavandi; Khalil Nasr Esfehani; Zienab Dehghan Mohammadi (Mashhad University of Medical Sciences, 2017)
Objective: Arctium lappa (burdock), (A. lappa) root has hypoglycemic and antioxidative effects, and has been used for treatment of diabetes in tradition medicine. This study was conducted to evaluate the antidiabetic and hypolipidemic properties of A. lappa root extract on nicotinamide-streptozotocin (NA-STZ)-induced type2 diabetes in mice.Materials and Methods: In this investigation, 70 adult male NMRI mice (30-35g) randomly divided into 7 groups (n=10) as follow: 1-control, 2-type 2 diabetic mice, 3-diabetic mice that received glibenclamide (0.25 mg/kg) as an anti-diabetic drug, 4, 5, 6 and 7- diabetic and normal animals that were pre-treated with 200 and 300 mg/kg A. lappa root extract, respectively, for 28 days. Diabetes has been induced by intraperitoneal injection of NA and STZ. Finally, the blood sample was taken and insulin, glucose, SGOT, SGPT, alkaline phosphatase, leptin and lipid levels was evaluated.Results: Induction of diabetes decreased the level of insulin, leptin and high density lipoprotein (HDL) and increased the level of other lipids, glucose, and hepatic enzymes significantly (p